2017
DOI: 10.1186/s13287-017-0659-2
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of hypoxia-inducible factor 1 alpha improves immunomodulation by dental mesenchymal stem cells

Abstract: BackgroundHuman dental mesenchymal stem cells (MSCs) are considered as highly accessible and attractive MSCs for use in regenerative medicine, yet some of their features are not as well characterized as other MSCs. Hypoxia-preconditioning and hypoxia-inducible factor 1 (HIF-1) alpha overexpression significantly improves MSC therapeutics, but the mechanisms involved are not fully understood. In the present study, we characterize immunomodulatory properties of dental MSCs and determine changes in their ability t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 41 publications
(49 reference statements)
1
67
0
Order By: Relevance
“…37 The overexpression of hypoxia-inducible factor 1 in MSCs inhibits the differentiation of DCs and strengthens the immunosuppressive function of CD14 + monocytes. 38 Thus, hypoxia might induce MDSC differentiation by modifying MSCs. In addition, according to Whiteside TL, MSCs that have been reprogramed by tumors deliver exosomes to immune cells, such as macrophages, in the TME and enhance their protumor functions.…”
Section: Discussionmentioning
confidence: 99%
“…37 The overexpression of hypoxia-inducible factor 1 in MSCs inhibits the differentiation of DCs and strengthens the immunosuppressive function of CD14 + monocytes. 38 Thus, hypoxia might induce MDSC differentiation by modifying MSCs. In addition, according to Whiteside TL, MSCs that have been reprogramed by tumors deliver exosomes to immune cells, such as macrophages, in the TME and enhance their protumor functions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, stabilizing HIF1α through loss of the factor inhibiting HIF (FIH) or through the oxidative dimerization of the prolyl hydroxylase domain protein 2 (PHD2) facilitates metabolic adaptation to hypoxia 30,35 . Previous studies showed that HIF1αoverexpressed MSC exhibits high immunomodulatory effects and high resistance to hypoxia-induced apoptosis 36,37 . Taken together, the metabolic reprogramming of MSC by HIF1α regulation can be a promising strategy to improve MSC-based therapies.…”
Section: Introductionmentioning
confidence: 99%
“…(23,24) HIF-1a has been further demonstrated to participate in various cell functions such as proliferation, angiogenesis, and immunoregulation, and is currently considered as one of the master regulators of the stemness. (25)(26)(27) Therefore, we have demonstrated the upregulation of HIF-1a upon culturing in BMC-CM under normoxic conditions. Intracellular upregulation of HIF-1a under hypoxia is generally considered to be primarily due to the oxygen-dependence of its degrading enzyme, but not from an increase in its production.…”
Section: Discussionmentioning
confidence: 76%